FEM modelling of hydrogen embrittlement in API 5L X65 steel for safe hydrogen transportation - Shaghayegh Nazar; Sebastian Lipiec; Edoardo Proverbio (Journal of Materials Science: Materials in Engineering)
Abstract Hydrogen is crucial for decarbonization efforts due to its abundance, environmental friendliness, and versatility. To maximize its potential, an efficient transportation infrastructure is essential. While utilizing the natural gas pipeline network for transporting hydrogen is cost-effective, hydrogen embrittlement (HE) poses a significant challenge. When hydrogen enters the metal, it significantly compromises its fracture toughness. This study investigates the impact of high-pressure hydrogen on the mechanical properties of API 5L X65 carbon steel through a combined experimental and computational approach. To quantify the extent of HE, tensile tests were performed on identical specimens, one set pre-exposed to high-pressure hydrogen and another set kept in an inert environment for comparison. Finite element modelling, employing the Bai-Wierzbicki material model (BWMM), was used to simulate the material behaviour under large plastic deformations and correlate with experimental results. This synergistic approach integrates experimental data with simulations, creating a framework for predicting and preventing catastrophic failures.